Management of Cities and Regions - Bobek, Vito (IntechOpen, 2017)
Cities and regions represent the driving force of development in economic, social, and cultural life and reflect the spatial organization of human society. Furthermore, strategic urban regions are becoming increasingly important players in the global economy, as the impact of national states decreases while the impact of cities and urban regions is increasing. The process of globalization is reflected in the tendency for gaining competitiveness and efficiencies of global trends. Once cities and regions have identified where they are, they need to decide where they want to be in the future. And to do this, they need to understand the significant trends that will influence the direction in which the future unfolds. Managing the identified capitals (four of them are subject of the sections in this book) effectively means taking a holistic approach, since each of the capitals depends on the others. The necessity of taking a holistic approach is one of the themes to emerge particularly strongly from the knowledge-based economy.